Towards the Rational Choice Theory in The Asian Approach to International Law - Suleiman, M. Ajisatria (Indonesian Journal of International Law, 2011)
The notion of “Asian approach to international law” refers to the international political relations of and among the Asian countries as well as the development of international law, and how the two dynamics interact between each others. A comprehensive analysis of the issues thus requires one single analytical tool that can encompass both issues at hand. Interestingly, at present research discussing the most appropriate methodology remains under-developed, as scholars mostly focus on particular case studies. The article offers the “rational choice theory” as the first stepping stone for further theoretical development and practical application. The rational choice theory, in essence an economic theory that deals with individual decision making, has been a valuable tools in assessing international relations from an institutionalism paradigm, and it has started to gain its importance in the field of economic analysis of international law. Therefore, I argue that the theory will provide an alternative insight of the “Asian approaches to international law” to the conventional theories of cultural differences (the west vs. the east) or political economy (developed countries vs. developing countries). I will first discuss the issues that conventional theories fail to address, and display how the rational choice theory can fill in the gap. For further practical implementation, I elaborate briefly several international law issues in the ASEAN context from the economics of rational choice perspective, namely on the principle of non-intervention and the institutionalization of human rights.